Xerodermic idiocy in identical twins. Issue 4 (December 1974) - Raju, L.; Adam, B. A.
Abstract : Identical twin girls with the xerodermic idiocy syndrome (xeroderma pigmentosum, neurological complications, and mental retardation) are described. Monozygosity was established by clinical features, blood types, and dermatoglyphics. Biochemical studies were normal but an electroencephalogram showed diffuse disturbance of cerebral function in both twins. Their bone age was retarded by about two years. A skin biopsy showed hyperkeratosis, atrophy of the rete ridges and hyperpigmentation of the basal cells, but no malignant change. The absence of malignant change was thought to be due to avoidance of sunlight. Neither consanguinity nor clinical evidence of the disease was present in the parents. A mutant gene of large effect is thought to be the cause of the syndrome. The underlying pathogenesis of the skin lesion is briefly discussed.